Industrial Estate Development: Challenges And Opportunities In Strengthening Competitiveness Of Manufacturing Industries - Sri Sarjana; Nur Khayati (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2018)
Competitive strategy is required by every business unit to win the competition in the uncertain and turbulent business environment especially in manufacturing industry. Development and distribution new industrial estates located in Java and outside Java by the Indonesian government in an effort to win the global competition in the manufacturing industry. This study empirically investigates the role of human capital, infrastructure, supply chain, science and technology on competitive strategy in business units at industrial estates and its impact on strengthening the competitiveness of manufacturing industries. The author conducted a survey on the best-performing industrial estate to test hypothesis and analyze the survey results using structural equation modeling. The results concluded that human capital, infrastructure, supply chain, science, and technology have a positive influence on competitive strategy and have a positive impact on the competitiveness of manufacturing industries especially located in industrial estates. In addition, the importance of choosing the right competitive strategy will greatly determine how big this business has superior competitiveness compared to its business competitors. This research is expected to be the reference for business units and manufacturing industries to be used as one of the considerations in the development of industrial estate that is being built and developed by the current government in order to get the best competitiveness.